Dye degradation and kinetics of online Electro-Fenton system with thermally activated carbon fiber cathodes - Ergan, Basak Temur; Gengec, Erhan (Elsevier Sci Ltd, 2020)
In this study, the effect of the gas type (N-2 or CO2) and activation time (0 - 10 h) on the thermal activation of carbon fiber (CF) electrodes being used as the working electrodes was tested in an Electro-Fenton (EF) system with Pt anodes; this was aimed at achieving the total organic carbon (TOC) removal for the Acid Orange 7 (AO7) dye. An EF experimental system was established to perform online analyses that were different from the majority of those in the literature. Furthermore, to test the effectiveness of the EF process parameters, the cathodic potential (0.5-2.5 V) and Fe2+ concentration (0.2 -1 mM) were investigated. The initial solution dye concentration (0.1 mM), pH (3), and electrolyte concentration (50 mM) were held constant in this study. In an undivided glass reactor, dry air was supplied (16 L/h) to the system in batch mode, and a 600-ml dye solution was added. The optimum dye and TOC removal efficiencies at 0.8 V with 0.3 mM of Fe2+ by using CF activated at 900 degrees C under N-2 for 5 h were 92.9 % at 15 min and 84.0 % at 120 min. In contrast, a kinetic analysis was performed using data from an online analysis system. Accordingly, the kinetic study of the degradation reaction was evaluated in two stages, namely, for the first 3.2 min and for the subsequnet time frame. In addition, the CF electrode was found to be a promising electrode for electro-oxidation systems, with augmentaions in the electroactive surface area and crystallite size by 46.64 % and 17.15 %, respectively.
Keywords: Electro-Fenton system; Carbon fiber; Thermal activation; Acid Orange 7; Degradation kinetics; Cylindrical cathode